STUDENTS PERCEPTION ON LECTURERS’ COMPETENCE DURING ONLINE LEARNING - Paulina Erawati Paramita, (JOEL: Journal of Educational and Language Research, 2021)
COVID-19 PANDEMIC has fundamentally changed learning activities in universities. Advances in technology and information communication have greatly helped the world of education. Learning is no longer done rigidly in the classroom, it also can be online. With the occurrence of social changes like this, our lecturers are divided into three groups. Then some are stressed but can follow, and some are left behind altogether. This is often experienced by senior lecturers who are approaching retirement. this study was conducted to describe the students’ perception from 156 fourth-semester students toward Widya Dharma University lecturers' competence during the Covid-19 Pandemic. the objectives of this research are to describe student perceptions of the competency of lecturers in delivering online learning at Widya Dharma University Pontianak and to analyze which competency to improve. Overall the result showed that most of the lecturers possess the four competencies in teaching during the COVID19 Pandemic